Deducing salinity from Chlorophyll-a using EO-1 Hyperion satellite imagery: A case study in Modaomen and Shawan waterway, Pearl River Estuary, South China - Ligang Fang; Shuisen Chen; Junping Qian (2010 18th International Conference on Geoinformatics, 2010)
Because of increasing marine intrusion into the Pearl River Estuary (PRE) of South China, the salinity has become one of the important and necessary hydrological and water quality monitoring parameters. In this research, we examined the relationships between the reflectance from EO-1 Hyperion satellite imagery and water surface salinity based on the in-situ spectra analysis model of the river water color component, in an attempt to deduce salinity from Chlorophyll-a ([Chl-a] in mg/m 3 ) using remote sensing technique. The study sites were the Modaomen and Shawan waterway in the Pearl River Estuary, Guangdong Province, South China. The studied samples (spectra, salinity and Chlorophyll-a concentration) were from 32 different locations of the waterways on December 18 and 19, in 2006. The studied field covered a large variety of optically different waters, the Chl-a concentrations varied between 4.81 and 92.6 mg/m 3 . The linear relationships between in-situ reflectance and Chl-a concentration were analyzed based on the single band, band ratios and their varieties, which were performed in MATLAB6.5 (Math works) using the "statistic analysis module". We found a strong positive linear relationship between in-situ reflectance ratio (R 704 /R 513 ) and Chl-a concentration (R 2 =0.92, P<;0.001). Additionally, we also found an indicator of marine intrusion location (at about 0.45 0 / 00 , a drinkable water quality standard) with sharp Chlorophyll-a concentration drop. Therefore, we were able to develop a new method of deducing surface salinity of the river estuary from the calibrated EO-1 Hyperion reflectance data. The EO-1 Hyperion derived surface salinities were validated using pointing observation data that were collected on December 21 2006, and synchronous with EO-1 Hyperion satellite imagery acquisition. The methodology of deducing salinity from Chl-a concentration provides potential to monitor coastal saltwater intrusion and provides the water supply and conservancy authorities with referenced spatial information to understand and manage the estuarine marine intrusion.